An Analysis on Teacher’s Strategy in Teaching Reading Comprehension at SMP YLPI Marpoyan Pekanbaru - Dilla Septianda; Shalawati (DISCOVERY JOURNAL, 2022)
This study was carried out to know what is the strategy used by the teacher in teaching reading at SMP YLPI Marpoyan Pekanbaru. The researcher expected the more teaching strategy is applied by the teachers in teaching reading, the more students enjoyable and understand how to be good reader. Design of this research as descriptive qualitative design, in which researcher describe strategy of teaching reading used by teachers to students at SMP YLPI Marpoyan Pekanbaru. This research had only one variable, it was strategy of teaching reading that used by teachers. The teachers utilized two strategies in teaching reading of the first and third year students in the classroom namely: Repeated Reading strategy and SQ3R strategy. The teachers utilized generally the indicator of the Repeated Reading strategy that they utilized in classroom. Total points of strategy on teacher A utilizing SQ3R strategy 4 points and the total points of strategy on teacher B utilizing SQ3R strategy 5 points. It can conclude that the teacher utilized generally the indicator of the strategy that her utilized in teaching reading comprehension in the classroom. Result of interview as additional information to know teacher teaching learning process used Repeated Reading and SQ3R strategies. Teacher ever used SQ3R technique and Repeated Reading strategies in teaching reading comprehension in previous class. The writer observed, she used material appropriate with the strategy. Teacher utilize this strategy in order to make students easy in comprehend learning material, since they frequently reread the content and discover the translation of difficult words, so it make them straightforward the understanding content.